Modelling an intelligent interaction system for increasing the level of attention - Durães, Dalila (2017)
Learning activities using technologies is one of the common education methods. Its advantages allow that students can learn with concepts more practical’s. However in this environment not all the students can be attentive. In this research an Ambient Intelligent System has been designed using biometrics behaviors for detecting learner inattentiveness. The learning attentiveness of a student can be determined precisely and the teacher has access to these results and might improve news strategies.